Investigation of electromyographic activity during salat and stretching exercise - Ibrahim, Fatimah; Ahmad, Siti Anom
Salat is a formal prayer practice by all Muslims. When performing salat, it involves with several movements namely standing, takbeer, bowing, prostration and sitting. The study was to quantify and compares the muscle activity (surface electromyographic signal) during Salat and stretching exercise. Three main movements in Salat (takbeer, bowing and prostration) and similar stretching exercises to the Salat movements were investigated. Thirty one male and female volunteers were participated in this study. The activity of the four investigated muscles: biceps brachii, triceps brachii, pectoralis major and upper trapezius were recorded during salat and stretching movements. The recorded signals were then analyzed using root mean square analysis. The results indicate similar muscle contractions activities during salat and stretching exercise. Even though, the root mean square values during stretching exercise is higher, a t-test shows there is statistically no significant difference between these two movements